Productivity improvement of low lying area with litchi (Litchi chinensis) based integrated system - PATEL, R K; SRIVASTAVA, KULDEEP; PANDEY, S D; KUMAR, AMRENDRA; PURBEY, S K; NATH, VISHAL (The Indian Journal of Agricultural Sciences, 2020)
The present study was carried out at ICAR-National Research Centre on Litchi, Muzaffarpur during 2014-2017 for sustained productivity, profitability, employment generation and soil health. Four different models comprised of rain water harvesting, fish culture, and intercropping of annual and vegetable crops with litchi (Litchi chinensis Sonn.) + banana and litchi+papaya in different combinations on pond dykes. Rain water accumulated in the ponds during rainy season with the storage capacity (7.29 million litre water) varied from of 1.62-2.16 million litre of water per pond. Among different models, model 1 recorded the highest total system productivity in terms of LEY (25.49 t/ ha), production efficiency (140.67 kg/ha/day), net return (₹ 159950/ha) and system economic efficiency (438.23 ₹/ ha/day). Sustainable value index (SVI) among the models varied due to different component and expressed 2 to 3 time’s higher value than existing system. Model 1 recorded highest SVI (0.78) and existing model (0.25) recorded lowest. Relative production and economic efficiency of the different models were also computed over the crop based existing system and value ranged from 521.72 and 67.64 in model 4 to 529.38 and 116.15 in model 1, respectively. Integration of fish, fruits, vegetable and crop component in the system showed greater employment opportunity and it was almost double than the crop based existing system. The highest employment generation was observed in model 1 (331 man-days/ha/year) as compared to existing system (150 man-days/ha/year). Marked improvement in soil health status (pH, EC, soil organic carbon and NPK) was observed as compared to initial soil status after three years of study.